Effect of organic sources and nutrient levels based SSNM on soil nutrient status and uptake of safflower (Carthamus tinctorious L.) - Hiremath, K. A.; Basavaraj Biradar (Annals of Agricultural Research, 2023)
An experiment was conducted at College of Agriculture, Bheemarayanagudi, UAS, Raichur during rabi season of 2021-22 to know the effect of organic sources and nutrient levels on soil nutrient status and their uptake by safflower. The results revealed that significantly higher soil available N, P2 O5 and K2 O (182.17, 24.13 and 352.91 kg ha-1, respectively) and total NPK uptake (57.56, 59.80 and 61.24 kg ha-1, respectively) were recorded with application of FYM @ 5 t ha-1compared to application of city compost @ 1 t ha-1. Further, this treatment was known to produce significantly higher plant height (85.95 cm), leaf area per plant (58.07 dm2 ), total dry matter accumulation (121.59 g plant-1), 100 seed weight (6.31 g), seed weight per plant (27.35 g) and seed yield (1467 kg ha-1) and stalk yield (2216 kg ha-1), Among different levels of nutrients, significantly higher available N, P2 O5 and K2 O (187.05, 25.87 and 354.18 kg ha-1, respectively) and total NPK uptake (57.92, 60.81 and 63.19 kg ha-1, respectively) by crop were noticed with SSNM based on STCR equation + micronutrients Zn @ 25 kg ha-1 + S @ 10 kg ha-1 as compared to other nutrient levels. Further this treatment resulted significantly higher plant height (87.82 cm), leaf area per plant (61.88 dm2 ), total dry matter accumulation (126.25 g plant-1), 100 seed weight (6.56 g), seed weight per plant (29.37 g), seed yield (1508 kg ha1 ) and stalk yield (2308 kg ha-1). Application of FYM @ 5 t ha-1recorded higher gross (Rs. 80,699 ha-1) and net returns (Rs. 51247 ha-1) compared to other treatments. SSNM based on STCR equation + micronutrients Zn @ 25 kg ha-1 + S @ 10 kg ha-1registered higher gross and net returns (Rs. 82,964 ha-1and Rs. 54,540 ha-1 respectively,) compared to other nutrient levels.